Optimization of osmotic pressure swelling method in the process of hemoglobin extraction from red blood cells - ZHANG Honghui; ZHOU Wentao; HAO Shasha; WANG Hong; LIU Jiaxin; YANG Chengmin; LI Shen; LI Fengjuan (Zhongguo shuxue zazhi)
[Objective] To extract hemoglobin (Hb) from red blood cells using osmotic pressure swelling method, expected to achieve a hemoglobin dissolution rate of ≥80% and a cell membrane integrity rate of ≥70%. [Methods] Human umbilical cord blood red blood cells were used as raw materials and phosphate buffer solution was used as the swelling solution for red blood cells. A three factor three-level orthogonal experiment (n=3) was conducted to determine the optimal matching conditions for selecting the osmolality molar concentration of phosphate buffer solution, pH value of hypotonic phosphate buffer solution and volume ratio of hypotonic phosphate buffer solution to washed red blood cells. Red blood cell swelling solution samples (n=6) were prepared by the optimal matching conditions and the original process conditions. The hemoglobin dissolution rate and cell membrane integrity rate were checked. In the expanded comparative experiment, red blood cell swelling solution samples (n=6) were prepared by the optimal matching conditions and the original process conditions, which was filtered by ultrafiltration membranes. The filtration time and hemoglobin yield were checked. [Results] The optimal matching conditions for preparing red blood cell swelling solution were obtained through orthogonal experiment as follows: osmotic pressure molar concentration was 30 mOsmol/Kg, pH was 7.8, and phosphate buffer to red blood cell volume ratio was 6∶1. On the basis of the above conditions, the red blood cell swelling solution sample was compared with the original process sample: the hemoglobin dissolution rate was (82.4±1.8)% vs (78.6±3.0)% (P<0.05), and the cell membrane integrity rate was (65.8±4.0)% vs (28.7±2.3)% (P<0.05). In the expanded comparative experiment, the optimal matching conditions were compared with the original process conditions: filtration time(s) (327±9) vs (434±13) (P<0.05), and hemoglobin yield was (72.3±1.2)% vs (66.0±1.4)% (P<0.05). [Conclusion] Compared with the original preparation process, the hemoglobin extraction process which optimized through orthogonal experiments greatly reduces the cell membrane fragmentation rate and minimizes the entry of cell membrane matrix into the target solution, ensuring a slightly higher hemoglobin dissolution rate, and reducing the preparation difficulty for the subsequent cell membrane separation and further purification.